Políticas de educação em prisões (2011-2020): conquistas e desafios no estado de Pernambuco - Barros Filho, Armando Dantas de (2020)
The research aimed to understand how public policies for education in prisons in Pernambuco are being implemented. It started from a systematic review of the literature from the perspective of Education in Human Rights, through analysis of the prison system and its difficulties in ensuring the right to education. To this end, it discusses educational policies based on the 1988 Federal Constitution and its democratic effects in the emergence of dialogue about education in prisons in Brazil. Critical Theory constitutes the analysis of this work, subsidized by the contributions of Critical Social Pedagogy and its relationship with Education in Human Rights, expanding the dialogue with the authors who study EJA in prisons today. It is qualitative research, characterized by a descriptive case study, with a time frame of educational policies in prisons in the period from 2011 to 2020, involving quantitative and predominantly qualitative data. It adopted as its field of research 20 schools located in prison units in Pernambuco and used semi-structured interviews as a data collection instrument. 12 teachers participated in the study, 04 school managers, 01 prison education coordinator, 04 prison unit directors, in addition to 01 representative for state education management and 01 teacher from the penitentiary system. For data analysis, the Content Analysis technique was chosen with a focus on Categorical Analysis. The quantitative results revealed that the average participation in educational activities in Pernambuco is 33.74%, representing the third largest participation in prisons, until December 2019, across the country. From a qualitative point of view, the results showed the subjectivities in EJA in prisons in Pernambuco, revealing the interests of students in the school process. EJA's contributions to prisons are evident in the perception of education professionals and the prison system. In the pedagogical scope, the interviewees highlight the obstacles and contributions to EJA in prisons. The institutional interfaces of educational policies in prisons are revealed. The limits and possibilities in prison education are highlighted by subjects research. Among them, the precarious relationship with prison agents and the lack of adequate physical and pedagogical structure stand out as limitations. Regarding the possibilities, the joint actions between the education and rehabilitation departments, the creation of a coordination of education in prisons and the expansion of the offer of schooling stand out. Another policy limit refers to the discontinuity of the partnership between MEC and DEPEN as of 2017, compromising the goals agreed to by the State Prison Education Plan. Finally, another result found is related to the evolution of education in prisons within the scope of basic, professional and higher education in Pernambuco. It is concluded that the EJA in prisons presents quantitative advances, however the biggest challenges are of a qualitative order, such as: under-valuing of teaching work, physical and pedagogical structuring of schools and the provision of higher levels of schooling. Analyzes and discussions at EJA in prisons revealed new scientific challenges, such as the development of qualitative indicators for education in prisons and the adhesion of public universities, in teaching and extension, in person and / or at a distance, in contexts of restriction and deprivation of liberty. The intention is to continue these studies.